Breathing the Air of Their Ancestors: The Influence of Ethnic-Racial Identity on School Connectedness for Native American Youths - Clark, Shawn (Journal of Ethnic and Cultural Studies, 2023)
In this Indigenous-grounded, transformative sequential explanatory study, the author examined the influence of ethnic-racial identity exploration on school connectedness in a sample of (n = 41) Native American youths attending a public school on a federally recognized Indian reservation. The students were enrolled in a Native American cultural immersion program. Participants completed a survey packet including a demographic form, an adapted cultural connectedness survey, and the MAC 5-A-Short Version six-item school connectedness subscale. While the results indicated that ethnic-racial identity exploration slightly impacted school connectedness, they were not deemed statistically significant. The author also captured youth participants' perspectives to develop a deeper understanding of how ethnic-racial identity exploration impacted school connectedness, identifying eight categories. These findings may help inform a broader development and application of a Native American way of knowing instructional model that contributes to strengthening school connectedness for Native American youths through ethnic-racial identity exploration.